Working Capital Management and Financial Performance of Manufacturing Sector in Sri Lanka - Rodrigo, W.S.L.; Chandima, S.H.I. (University of Jaffna, 2018)
Working Capital Management provides critical insight into the performance of the organizations and it plays an important role in any kind of industry, especially in the manufacturing sector. As an important indicator for measure the performance and viability of the organization, many managers involved considering the efficient management of Working Capital in the organization. Accordingly, the main purpose of this study is to identify the relationship between Working Capital Management and Financial Performance of the manufacturing sector in Sri Lanka. In Sri Lanka manufacturing sector is the second largest segment of the economy contributing significantly to the Gross Domestic Product of the country. For this study, data was collected from the manufacturing firms quoted on the Colombo Stock Exchange (CSE). As a sample size, this study used 30 manufacturing firms while the sample period of the study is five years from 2013 to 2017. The data was collected through the published annual reports of the respective companies. To examine the effect of WCM on performance, this study applied Return on Assets(ROA) and Return on Equity(ROE)as outcome variables whereas Cash Conversion Cycle (CCC), Current Financial Assets Ratio (CFAR) and Current Financial Debt Ratio (FDR) were used as explanatory variables. Since the study involves panel data, pooled OLS analysis has been carried out to arrive at the findings of the study. There is no significant relationship between CCC, CFAR, FDR, and outcome named ROA while CCC, CFAR, FDR, and ROE have a significant relationship, the findings reveal. The study also concludes that manufacturing firms in Sri Lanka need to concentrate on conservative Working Capital Management policy and improve their collection and payment policy.
Keywords: working capital management; colombo stock exchange; cash conversion cycle; current financial assets ratio; current financial debt ratio